Research on the effectiveness of the recruitment and selection process of Square Food and Beverage Ltd. - Mahbub, Ramisha Binta (Brac University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2019.